A tensão entre eficiência e inclusão nas redes de cooperação: um estudo Multicasoscha Schmidt - Schmidt, Joel Ricardo Rocha (Universidade do Vale do Rio dos Sinos, 2016)
A growing number of small and medium-sized enterprises have been using cooperation networks to look for ways to improve bargaining power and the access to strategic resources that they would not obtain on their own. These networks have usually been managed by a board of directors as an Network Administrative Organization (NAO). There are some tension and contradictory logic inherent in the business model, like the tension between efficiency and the need to include members into the decision making process (PROVAN; KENIS, 2008). The objective of this study is to analyze how the critical contingency factors – trust, number of participants, goal consensus and Need for Network-Level Competencies – have influence in the tension between efficiency and inclusiveness, and what are the mechanisms to minimize it. A descriptive-qualitative-multiple-case study was carried out with leaders from three cooperation networks of building supplies, which operate in São Paulo, Paraná and Rio Grande do Sul. The research reveals that there is a relation between the critical contingency factors described by Provan and Kenis (2008) and the tension between efficiency and inclusiveness. These factors affect the orientation of the network leadership for efficiency or inclusion, according to the level presented. In the pursuit of balance between efficiency and inclusion, the networks mainly use the connection and integration mechanisms among units and functions, and the social control and coordination systems. As a theoretical contribution, the study confirmed the existence of a relation between critical contingency factors and the efficiency/inclusion tension. Furthermore, it brought to light two additional contingency factors related to tension – network management trust and the geographical dispersion of its members - and also found that management through Network Administrative Organization does not guarantee the efficiency in the decision making process. As managerial contributions, three recommendations were given to the leaders: the concession of greater autonomy to the network executive managers and their internal teams; promoting the clustering of associated stores; and enhance appreciation to the contact moments with associates..
Keywords: Governança de redes; Tensões de governança; Redes de cooperação; Network governance; Network tensions; Cooperation network; ACCNPQ::Ciências Sociais Aplicadas::Administração